Rehabilitation of partially edentulous arch using semi precision attachment: an aesthetic approach - Nuriyanto, Ainy Fitri; Salim, Sherman; K., Michael Josef K. (Indonesian Journal of Prosthodontic, 2021)
The restoration of normal function and esthetic appearance with a dental prosthesis is a major challenge in the rehabilitation of patients who have lost their teeth. In such situation, a fixed removable prosthesis allows favorable biomechanical stress distribution along with restoration of esthetics, phonetics, comfort, hygiene and better postoperative care and maintenance. Prime function of attachment retained partial denture is to distribute the masticatory forces to the wide area thereby reducing the damage to the abutments, soft tissues and bony ridges in addition to improved esthetics and proprioceptive responses. In this case series patient’s esthetic and functional requirements were fulfilled with attachment retained cast partial denture using semi-precision attachments